MCITP Microsoft SQL server 2005 data access design and optimization study guide - Miller-White, Marilyn (Wiley, 2007)
As your essential guide to Microsoft's new SQL Server 2005 certification (exam 70-442), this book offers you practical and in-depth coverage. Full coverage of all exam objectives is presented in a systematic approach so you can be confident you're getting the instruction you need for the exam.